Effect of mineral matter removal on pyrolysis of wood sawdust from an invasive species. Issue 4 (16th February 2016) - Messina, L. Gurevich; Bonelli, P. R.; Cukierman, A. L.
ABSTRACT: Kinetics of the pyrolysis of wood sawdust from the invasive species Parkinsonia aculeata, untreated and demineralized by a mild acid treatment, is comparatively investigated in order to examine the effect of the removal of minerals naturally present in the biomass. Non-isothermal thermogravimetric analysis from room temperature up to 500°C is applied for this purpose. Demineralization shifts the process onset and the maximum degradation rate to higher temperatures, and leads to enhance the activation energy from 56 to 60 kJ mol –1, pointing to a catalytic role of alkaline and alkaline earth metals in the biomass. Likewise, the three kinds of pyrolysis products (gas, bio-char, and bio-oil) are obtained from experiments performed in a bench-scale installation at 500°C. Yields and physicochemical characteristics of the pyrolysis products are determined. The pronounced reduction in the content of metals in the sawdust leads to increase bio-oil yield in around 10%, the specific surface area of the bio-char, from ≈ 2 to ≈ 74 m 2 g –1, and the higher heating value of all the pyrolysis products.